Evaluation of Seedling Age and Level of Nitrogen on Phenology Yield and Agrometeorological Indices for T-Aman Rice (Journal of Environmental Science and Natural Resources, 2025)
Cereal crops are more sensitive toward climate change. Consider this fact a field test was carried out through aman season of 2022 at Environmental field of faculty of Agriculture, BAU to study the influence of phenology, yield, and agrometeorological indices for T-aman rice. There experiment consist of two factorial RCBD design having seedling age (20, 30, and 40 days old) and nitrogen level (0 kg N/ha, 25 kg N/ha, 46 kg N/ha, and 80 kg N/ha) with three replications. Results showed that T-aman rice exhibited higher agrometeorological indices; thermal use efficiencies, grain yield, and straw yield were found in 20-day-old seedlings followed by 30-day-old seedlings, while the lowest values were obtained with 40-day-old seedlings. Moreover, nitrogen being used as a fertilizr management practice increased the agrometeorological indices, thermal use efficiencies, grain yield, and straw yield. The highest values were observed with N3 treatment (80 kg N/ha), followed by N2 (46 kg N/ha), while the lowest values were recorded in the control treatment. Thermal utilization efficiencies showed a strong correlation and regression with biological yield. Therefore, in addition to the heat requirement, the heat utilization efficiency is also a decisive factor for the crop yield.Environ. Sci. & Natural Resources, 14(1&2): 49-54, 2025